The Influence of Consumption Purpose on Consumer Preferences for Fruit Attributes: The Moderating Effect of Color Perception - Yihan Wang; Lingying Liu; Yangyang Wei (Foods)
With the increasing awareness of health among residents, consumers are paying more attention to their eating purposes and food safety when choosing fruits. This study aims to explore the impact of eating purpose on consumers’ preferences for fruits and fruit products under the mediation of color perception. The study obtained experimental data from 489 urban consumers in China through the Credamo data collection platform. Furthermore, four experimental groups were set up to propose six hypotheses based on the influence of eating purpose on consumer preferences for fruits and their products. The study utilized Likert scale questionnaires, chi-square tests, and variance analysis for data mining and cross-validation. The results indicate that the visual characteristics of fruits (especially color) affect the purchase preferences of consumers with different eating purposes. Approximately 65% of health-oriented consumers are highly sensitive to the color and nutritional value of fruits. They believe that fresh fruits are rich in natural nutrients and play an important role in maintaining health and preventing diseases. Meanwhile, around 62% of consumers with specific nutritional needs prefer processed fruit products, such as fruit preserves or dried fruits. These consumers have a weaker perception of color and focus primarily on the functionality of the fruits. Additionally, the study found that safety/taste preferences acted as a mediator and associative learning as a moderating variable. Around 58% of consumers indicated that their purchase preferences are influenced by safety and taste, and the relative importance of safety and taste preferences significantly mediated the relationship between eating purpose and purchase preferences. Under the moderating effect of associative learning, health-oriented consumers, when associative learning is activated, are about 45% more likely to choose fresh fruits. The study highlights consumers’ health-conscious perceptions in fruit selection, focusing on how color perception moderates the preference choices of different consumer groups based on their eating purposes. It emphasizes the need for businesses to adjust product positioning and marketing strategies according to consumer perceptions to promote broader healthy eating behaviors.